The Impact of Marketing Mix (7P’s) Towards Fish Feed Customer Satisfaction of PT. Central Proteinaprima in Sidoarjo Area - Yohannes Santoso (iBuss Management, 2015)
Customer satisfaction  is one of the  crucial factors  that determines  the performance of  a company.  In  Sidoarjo,  PT.  Central  Proteinaprima  competes  with another companies to control the animal feed market. This research was conducted  to determine the effect of the marketing mix  (7P's) towards customer satisfaction. Data  obtained  using  simple random sampling method  by distributing questionnaires to  132  respondents  in  Sidoarjo. Data  then  analyzed  using Multiple  Linear Regression Analysis. Results from this study indicate that the marketing mix (7P's) overall has significant influence towards fish feed customer satisfaction of PT. Central Proteinaprima in Sidoarjo. Individually, the price has a significant influence on fish feed customer satisfaction of PT. Central Proteinaprima in Sidoarjo.  Keywords: Marketing mix, Customer satisfaction